2016
DOI: 10.1371/journal.ppat.1005848
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Acute Cystitis Reveals Susceptibility Genes and Immunotherapeutic Targets

Abstract: Tissue damage is usually regarded as a necessary price to pay for successful elimination of pathogens by the innate immune defense. Yet, it is possible to distinguish protective from destructive effects of innate immune activation and selectively attenuate molecular nodes that create pathology. Here, we identify acute cystitis as an Interleukin-1 beta (IL-1β)-driven, hyper-inflammatory condition of the infected urinary bladder and IL-1 receptor blockade as a novel therapeutic strategy. Disease severity was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(103 citation statements)
references
References 70 publications
(81 reference statements)
1
91
1
5
Order By: Relevance
“…7C) and bacterial loads (Fig. 7A) for HVM277ΔhlyA, by comparison to the wild-type HVM277 strain, is in keeping with a previous study demonstrating that bladder IL-1b production was associated with increased bacterial colonization and that IL-1b-deficient mice were more resistant to CFT073 infection (61). On the other hand, another study reported that CFT073 loads in the urine were increased in Il-1b 2/2 mice (21).…”
Section: Discussionsupporting
confidence: 90%
“…7C) and bacterial loads (Fig. 7A) for HVM277ΔhlyA, by comparison to the wild-type HVM277 strain, is in keeping with a previous study demonstrating that bladder IL-1b production was associated with increased bacterial colonization and that IL-1b-deficient mice were more resistant to CFT073 infection (61). On the other hand, another study reported that CFT073 loads in the urine were increased in Il-1b 2/2 mice (21).…”
Section: Discussionsupporting
confidence: 90%
“…Причем нару-шение контроля выработки ИЛ-1β является как генети-чески обусловленной особенностью организма, так и инфекционно-зависимым процессом [15,16]. Авторы исследований выдвигают гипотезу о том, что острый цистит сходен по молекулярным механизмам с гиперво-спалительными заболеваниями [17][18][19], при которых была зарегистрирована терапевтическая эффективность ингибиторов IL-1β [20].…”
Section: рисунок 2 предполагаемая модель передачи сигнала через Tlr4unclassified
“…После активации TLR происходит активация образования целого ряда провоспалительных цитокинов (фактор некроза опухоли-α, интерлейкин-6 (IL-6), интерлейкин-17а (IL-17a), интерлейкин-1β (IL-1β), гранулоцитарный колониестимулирующий фактор (G-CSF) и т.д. ), участвующих в развитии воспаления, направленного на элиминацию возбудителя [32,33].…”
Section: рисунок 4 структура и лиганды для Toll-подобных рецепторов unclassified
“…Экспериментальные Поскольку вследствие генетически обусловленной особенности организма либо в результате инфекционного процесса при цистите происходит нарушение контроля выработки ИЛ-1β, предполагается терапевтическая эффективность ингибиторов IL-1β [32]…”
Section: современные перспективы терапии импunclassified